STRIDE BP international initiative for accurate blood pressure measurement: Systematic review of published validation studies of blood pressure measuring devices. Issue 11 (26th October 2019) - Stergiou, George S.; O'Brien, Eoin; Myers, Martin; Palatini, Paolo; Parati, Gianfranco; Kollias, Anastasios; Birmpas, Dimos; Kyriakoulis, Konstantinos; Bountzona, Ioanna; Stambolliu, Emelina; Anagnostopoulos, Ioannis; Karpettas, Nikos; et al.
Abstract: Blood pressure (BP) is a vital sign, and its measurement is essential for diagnosing and treating hypertension. The accuracy of BP monitors is therefore essential, but unfortunately very few devices available on the market have been validated using an established protocol. STRIDE BP (www.stridebp.org ) is an international nonprofit organization with the mission to improve the accuracy of BP measurement and the diagnosis of hypertension. It has a prestigious Scientific Advisory Board and operates in affiliation with the European Society of Hypertension, the International Society of Hypertension, and the World Hypertension League. STRIDE BP provides lists of accurate office, ambulatory, and home BP monitors. STRIDE BP performed a systematic review of 419 published validations (270 articles and 260 devices). In these publications, 50 (12%) of the validations were rejected compared with 129 (31%) rejected by STRIDE BP ( P < .001). Of 79 validations approved in publications but rejected by STRIDE BP, 7 (9%) were rejected due to device inaccuracy and 72 (91%) due to inadequate study quality (execution, analysis, and reporting). Errors in conducting and reporting published validations must be avoided. Peer review must ascertain that a comprehensive checklist of all aspects of a validation study have been adhered to. The implementation of a Universal Standard for device validation and the global dissemination of information on accurate devices by STRIDE BP are expected to improve the quality and accuracy of BP measurement, which should have a positive impact on the diagnosis and management of hypertension globally.